Habilidades práxicas orofaciais em crianças com desvio fonológico evolutivo e com desenvolvimento fonológico típico - Marini, Caroline (2010)
Many children, to the 4 or 5 years of age, already present acquired the contrasts of adult phonemic system. However, this process nor always occurs in accordance with the waited one, verifying alterations and shunting lines in speak of children. This study aimed to compare the orofacial praxis abilities in children with Tipical Phonological Development of Speech (TPDS) and with Phonological Disorder (PD). The research was composed for 50 children, who were divided in 30 with TPDS and 20 with PD, and ages between 4 and 8 years-old. The diagnosis of phonological disorder was determined by speech-language evaluations and complementary exams. The children were submit to the Test of Orofacial Praxis (BEARZOTTI et al., 2007), the Test of Articulatory and Bucofacial Praxis (HAGE, 2000) and the evaluation of Stomatognathic System (SS). The obtained results, in general, showed that the children with TPDS had present better performance than the Sequence Moviments carried through after verbal request and for the task of Verbal Praxis after imitation. Still, with the age increase, it had an improvement in the averages of the tests and when the tasks of praxis were carried through after verbal request, they were better than for imitation. Statistically significant results could be observed in relation to the age, for the Verbal Praxis, Orofacial Praxis and Sequence Movements after verbal request for the children between 6:0 and 8:01 years, and for Orofacial Praxis after verbal request for the aged 4:0 to 5:11 years. Thus, it s possible to conclude that the children with PD present more SS, Orofacial Praxis and Articulatory and Bucofacial alterations. Still, averages of rightness improve as age advance, and the children present more facility to realize the tasks after imitation than after verbal request, only. On this form, further studies can help develop this area still poorly developed.